Physiological responses in Alpine skiers during on-snow training simulation in the cold - Suzuki, E.; Ohya, T.; Ito, R.; Matsumoto, T.; Kitagawa, K. (International Journal of Sports Medicine, 2014)
This study examined the physiological responses to cold stimulus during intermittent high-intensity exercise simulating on-snow alpine ski training. 7 male alpine skiers performed intermittent high-intensity exercises composed of 4 bouts of cycling exercise at 140% VO2max intensity for 30 s with 10-min rests on a cycle ergometer in cold (1°C) and control (22°C) conditions. The subjects wore racing suits, middle layers and half pants designed for alpine skiers. Rectal temperature and mean skin temperature were lower in the cold condition than in the control condition (36.8±0.5 vs. 37.1±0.1°C and 28.4±0.6 vs. 33.3±0.6°C, respectively). Oxygen consumption during rests and the last 2 bouts of exercise was higher in the cold condition than in the control condition. Although plasma noradrenaline and serum triglyceride were higher in the cold condition than in the control condition, plasma glucose, adrenaline and serum glycerol were lower. Serum free fatty acid and plasma lactate concentrations did not differ significantly between the 2 conditions. These results indicate that a cold stimulus affects body temperature and energy metabolism and may lead to a decrease in exercise capacity in alpine skiers during on-snow training.